LOXOPROFEN NANOSPONGES: FORMULATION, CHARACTERIZATION AND EX-VIVO STUDY - HAMZA, MANAL Y.; ABD EL AZIZ, ZEINAB RAGHEB; ALY KASSEM, MOHAMED; EL- NABARAWI, MOHAMED AHMED (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of this study is to optimize a nanosponge formulation for Loxoprofen and then incorporating it into a gel formulation offering a controlled drug release, enhanced skin permeation and thus better bioavailability. Methods: Loxoprofen nanosponges were prepared using the emulsion solvent diffusion method and formulated using Polyvinyl alcohol, Ethylcellulose and Dichloromethane. The effect of the different formulation variables like ethyl cellulose: polyvinyl alcohol ratio, drug: ethyl cellulose ratio, stirring time, stirring speed, internal phase volume and external phase volume on the particle size, entrapment efficiency, production yield, polydispersity index and Zeta potential was investigated. The optimized nanosponge formulation was incorporated into a gel. The loaded gel was evaluated by in vitro release and permeation studies and the results were compared to that of a marketed formulation (Loxonin® gel). Results: The optimized formulation showed 67.29±1.19 % entrapment efficiency, 239.8±16.95 nm particle size and-8.32±0.87 mV Zeta potential. The drug was released slowly from the nanosponge-loaded gel where the cumulative percentage of drug released was only 77.71±0.42 % in 8 h where it was incorporated in the entrapped form while it was 99.31±0.64% from Loxonin® gel where it was in the unentrapped form. The cumulative percent of drug permeated through the skin from the nanosponge-loaded gel was 98.66±0.14% for 24 h while it was only 60.38±0.18% from Loxonin® gel. Conclusion: The nanosponge-loaded gel showed more sustained drug release and a better drug permeation when compared to a marketed gel (Loxonin® gel).